Women’s Empowerment Index in Cassava: An Innovative Tool for Gender Mainstreaming (Indian Journal of Extension Education, 2022)
Analysis of women’s empowerment in cassava was done among farm women and farmers who are involved in cassava cultivation in Kanyakumari district of Tamil Nadu. Snowball sampling technique was employed for collecting data using semi-structured interview schedule from 50 women and 50 men farmers involved in cassava cultivation. The women empowerment index in cassava was used for estimating the domains of empowerment and gender parity index. Results revealed that cassava women farmers were more empowered than their household male counterparts in the domains of community leadership and time allocation. Whereas, male farmers were more empowered than their female counterparts in production decision making, access to productive resources and control over use of income. It was found that the overall women empowerment score was 0.83 with 28 per cent of women in disempowered category.